Influence of Globalization and its Impact on Performance: Research on Network Ability - Bhaumik, Amiya; Aun Law, Kian; Fang, Jiemiao (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the author uses the term "born global firms" as a special term to describe such "accelerated" small and medium-sized enterprises that carry out international operations and uses the relationship network as the main research perspective and analysis framework. Although studies have shown that the relationship network as an opportunity recognition carrier plays a significant role in the accelerated international development of enterprises, it is important to identify and develop international opportunities for how born global firms build and manage relationship networks. Then it affects the key issues, such as international market development and performance improvement.